Using Force Field Analysis for Examining and Managing Stakeholders’ Perceptions of Mining Projects - Francis Pavloudakis; Philip-Mark Spanidis; Christos Roumpos (Materials Proceedings)
This article uses force field analysis (FFA) to examine the role of stakeholders in the lignite mining project of the Western Macedonia Region, Greece, which is entering the closure phase at an accelerated pace due to energy transition policies. The FFA is applied in four steps: identification of internal and external stakeholders; classification of them into groups according to their interest and influence on the project; assessment of each stakeholder’s strength in quantitative terms and graphical representation of it in a force field diagram; and management of stakeholders’ perceptions. The result of this article is the determination of a specific course of action that balances the benefits and impacts for all stakeholders.